Stages of recovery from depression in relation to clinical outcomes and consumer recovery processes - Low, Benjamin C. Y.; Lim, Kokkwang; Wong, Meiyin; Ooi, Sayleong; Oades, Lindsay G.; Yap, Chee Khong (International Journal Of Community Medicine And Public Health, 2019)
Background: Research on consumer-defined recovery from mental illness has been critiqued for a lack of quantitative evidence and conceptual clarity that has impeded further development of recovery-oriented services. This is especially true when it comes to models of the stages of recovery from mental illness. Qualitative studies have produced 20 distinct stage models with significant similarities but limited quantitative validation. The present study tests the convergent validity of one promising model in relation to psychosocial functioning, depression symptoms, and the processes that are thought to underpin consumer-defined recovery. Methods: Eighty-eight patients with depressive symptoms were recruited. Patient-rated and clinician-rated measures were used to assess participants’ current stage of recovery, depressive symptoms, psychosocial functioning, and their level of attainment on the processes of recovery. Results: Higher stages of recovery were associated with better depression symptoms, participant and clinician rated functioning, and several recovery processes that were repeatedly identified by past research. The effect sizes were consistently large. Conclusions: Evidence of convergent validity was found for the model under study. Together with previous research, results suggest that the model may be a promising description of the recovery process and could inform the development of recovery-oriented services.